Kazakhstan Nationwide Assessment of Climate-Change Related Risks and Formulation of Mitigation Strategy : Policy and Institutional Directions for Bolstering Climate Resilience in the Agriculture, Forestry and Energy Sectors - World Bank (Washington, DC, 2015)
This Policy Note outlines the most critical climate risks in coming decades, possible climate‐smart measures for reducing these risks, and a review of how current Government of Kazakhstan strategies and action plans address these issues.